Nutrient dynamics during photodegradation of plant litter in the Sonoran Desert. (January 2019) - Ball, Becky A.; Christman, Maximilian P.; Hall, Sharon J.
Abstract: Arid and semi-arid ecosystems are experiencing increased rates of atmospheric nitrogen (N) deposition, but the ecological fates of excess nutrients in aridlands are unclear given the few studies conducted in deserts compared to mesic ecosystems. Altered decomposition resulting from increased N availability may not be important in arid ecosystems with significant photodegradation, which may be less influenced by nutrient content than biologically-mediated decomposition. Additionally, nutrient dynamics during decomposition have been studied almost exclusively in mesic ecosystems. To understand the potential impacts of N deposition on mass loss and chemical dynamics during aridland decomposition, we assessed N and phosphorus (P) dynamics of decomposing litter in a long-term N + P enrichment experiment in both urban (+N deposition) and outlying areas (-N deposition) of the Sonoran Desert. Litter was decomposed with and without UV radiation for 9 months, measuring mass loss, litter chemistry, and bacterial biomass. UV radiation significantly accelerated mass loss and altered N and P dynamics, and there was an impact of the urban environment and experimental fertilization on nutrient dynamics. Overall, these patterns suggest that the aridland urban environment, where rates of N deposition are elevated, alters nutrient dynamics during decomposition but not the fraction of litter lost to photodegradation. Highlights: UV radiation accelerated litter mass and nutrient loss in the Sonoran Desert. An exception is that UV slowed mass and N + P loss in fertilized, urban litter. This suggests urban nitrophilic microbes may be sensitive to UV. Litter nutrient dynamics were altered by the urban environment and N + P enrichment. Immobilization, especially of P, was greater outside the city suggesting P limitation.